Pewarisan Trauma dan Konsep Ibu dalam Film Ali & Ratu-Ratu Queens: Analisis Teori Postmemory Marianne Hirsch - Putra, Jalu Norva Illa; Citrawati, Ni Putu Evi Wahyu (Universitas Ahmad Dahlan, 2023)
This research will look at the relationship between memory and literature, which is about the process of inheritance of memory. A film entitled Ali and The Ratu-ratu Queens was chosen to be the object of this research, which will look at the relationship between memory, trauma, and the process of inheritance. This study aims to determine the trauma of the other that is passed on to the self, its transmission process and also to identify the reconstruction of the trauma that is owned by the self. This paper will use a perspective of Postmemory theory from Marianne Hirsch. Postmemory is a theory that looks at the process of inheritance of trauma between generations. This theory will look at the process of Ali as second generation inheriting his father’s trauma. Furthermore, the identification that can be obtained is that the loss that Ali feels is the loss of an